Move to Live - Lawick, Justine van; Bom, Hans (Murmurations: Journal of Transformative Systemic Practice, 2024)
We, Hans and Justine, share the love of walking with many. To move proves beneficial for body and mind which are connected and interdependent. This article has three parts. We start with a brief introduction about movement with a focus on walking. The second part contains a dialogue about our own experiences with walking. Several themes are addressed: getting stuck and getting unstuck; the art of doing nothing useful; getting back to basics; the body thinks; time and duration; alone and together; silence. In the third part, we try to highlight the relevance of movement, both physical and also as a form of community action, for systemic practice, and its connection to change. We distinguish between first, second and third order changes.